Wives, Widows, Daughters, and Guildswomen: Female Workers in Sixteenth-Century Florentine Taverns and Inns - Desilva, Jennifer Mara; Didone, Samuel; Ni, Qiyouran (Renaissance and Reformation / Renaissance et Réforme, 2024)
Early modern Florentines depicted their taverns as wonderful and raucous places that were central to masculine sociability and a threat to female chastity. Many modern historians have followed this lead, presenting the history of Florentine taverns as a study of contemporary sociability and morality. In contrast to the male-centric tavern, this study explores sixteenth-century Florentine taverns as places of work employing many women in a variety of roles. Focusing on workscapes problematizes occupational gendering and considers how taverns involved the tavern keeper’s household and neighbours. Using guild, census, and judicial records, this study explores the spaces that some female tavern keepers, procuresses, and sex workers shared in an effort to reveal women’s work in a professional space previously considered to be exclusively male-dominated.